2009
DOI: 10.1159/000210692
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Weight Reduction on Eating Behaviors and Quality of Life: Influence of the Obesity Degree

Abstract: Background:To examine the effects of a short-term weight reducing program on body composition, eating behaviors, and health-related quality of life (HRQL) of sedentary obese women characterized by different obesity degrees. Methods:44 women with a BMI under 34.9 kg/m2 and 39 women with a BMI above 35 kg/m2 were studied. Fat mass and lean mass (electrical bioimpedance), eating behaviors (Three-Factor Eating Questionnaire), and HRQL (36-item short form, SF-36, questionnaire) were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…An increase in total restraint, flexible control or rigid control has been shown also by others to predict weight changes over time (43)(44)(45) . However, with regard to BMI, the role of flexible control seems to be prevailing as in DELIGHT (17,18,46) .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…An increase in total restraint, flexible control or rigid control has been shown also by others to predict weight changes over time (43)(44)(45) . However, with regard to BMI, the role of flexible control seems to be prevailing as in DELIGHT (17,18,46) .…”
Section: Discussionmentioning
confidence: 72%
“…It encompasses two distinct behavioural subscales of eating behaviour: rigid control, characterized by an 'all or nothing' approach, and flexible control, which comprises a 'more or less' approach to weight and eating (16,17) . In studies validating these psychological constructs, rigid control was associated with a higher BMI and disordered eating patterns, whereas flexible control was associated with a lower BMI and a more pronounced weight loss (18)(19)(20)(21)(22) . However, information on the association between cognitive control and central obesity, prediabetes and dietary food patterns is currently limited.…”
mentioning
confidence: 99%
“…The positive impact of a successful weight-loss program on the psychological functioning of the obese was reported by other authors: the achievement of even a small body weight loss, results in an improved quality of life in the aspect of psychological health and social functioning, [11][12][13] increased sensation of self-efficacy and satisfaction with one's body, 14 and improved psychological wellbeing. 15 However, in our study, we observed that the perception of one's own situation as threatening or harmful became weaker as early as after the first 5% body mass reduction, and thereafter was seen more as a challenge.…”
Section: Discussionmentioning
confidence: 54%
“…Instead, the differences in this regard are typically analyzed after achieving a predefined body mass reduction. [11][12][13][14][15] Regardless of the dynamics of the process, the achievement of a target weight reduction improves the wellbeing and functioning of the obese. It is therefore essential to increase the chances of success of such individuals undertaking a weight-loss program.…”
Section: Discussionmentioning
confidence: 99%
“…Although eating behaviors have been mostly studied as predictors for weight change or weight status,4,5,6,7,8,9,10,11,12 some weight-loss studies found the impact of weight-loss on eating behaviors 13,14. After short-term weight reduction, dietary restriction scores increased, while disinhibition scores decreased 13,14.…”
Section: Introductionmentioning
confidence: 99%